Higher preoperative left atrial volume index predicts lack of mitral regurgitation improvement after transcatheter aortic valve replacement. Issue 5 (May 2020) - Dominici, Carmelo; Salsano, Antonio; Nenna, Antonio; Spadaccio, Cristiano; Barbato, Raffaele; Mariscalco, Giovanni; Santini, Francesco; Bashir, Mohamad; El-Dean, Zein; Chello, Massimo
Abstract : Background: Moderate-to-severe mitral regurgitation is present in 20–35% of patients undergoing transcatheter aortic valve replacement (TAVR) and the current literature lacks simple echocardiographic parameters, which can predict post-TAVR changes in mitral regurgitation. The aim of this study is to investigate the echocardiographic predictors of improvement or worsening of mitral regurgitation in patients undergoing TAVR with moderate-to-severe mitral regurgitation. Methods: This retrospective study included 113 patients who underwent TAVR with preoperative mitral regurgitation grade at least 2. Patients with concomitant coronary artery disease requiring treatment were excluded. Mitral regurgitation was related to the annular dilatation or tethering mechanism in all patients. Preoperative and postoperative echocardiographies were compared in terms of mitral regurgitation and other commonly measured parameters. Results: After TAVR, a reduction in mitral regurgitation was observed in 62.8% of cases. On the basis of the difference between postoperative and preoperative echocardiograms, 71 patients had improved mitral regurgitation, whereas 42 patients had stable or worsened mitral regurgitation. After analyzing preoperative echocardiographic parameters with regard to this group difference, left atrial volume index (LAVI) was the only variable that was different between groups (33.4 ± 4.8 ml/m 2 in improved mitral regurgitation vs. 39.8 ± 3.0 ml/m 2 in not improved mitral regurgitation, P  < 0.001). In a multivariable logistic regression model, a LAVI increase was associated with lack of an acute reduction in mitral regurgitation (odds ratio = 1.41, P  < 0.001) after adjustment for age and preoperative serum creatinine. Conclusion: Higher preoperative LAVI is a determinant predictor of lack of an acute reduction in mitral regurgitation after TAVR, and LAVI could be used as a stratifying tool to tailor the treatment strategy and the timing of the procedures. However, validation of these results and long-term outcomes are warranted to support those conclusions. Abstract : Supplemental Digital Content is available in the text